2013
DOI: 10.1002/poc.3243
|View full text |Cite
|
Sign up to set email alerts
|

Interaction of ionic liquids with the surface of silica gel using nanocluster approach: a combined density functional theory and experimental study

Abstract: Silica gel‐confined ionic liquid (IL) is a class of heterogeneous catalysts with broad catalytic applications. Leaching of the IL from the surface of the support is the major drawback of these catalysts, which reduce the catalyst efficiency during the chemical reactions. To investigate the effect of the hydrogen bonding on the leaching phenomena, the interaction between the 1‐ethyl‐3‐methylimidazolium‐based IL with various anions (Cl−, Br−, HSO4−, NO3−, BF4−, and PF6−) and the surface of the silica gel were st… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 14 publications
(8 citation statements)
references
References 19 publications
(31 reference statements)
0
7
0
Order By: Relevance
“…In previous studies, ion adsorption of ILs on the silica surface was suggested to occur via H-bonding. ,, It has been reported that the N–H protons in the cation of PILs also form extensive and directional H bonds with anions forming H-bonded cation–anion aggregates in neat PILs. , As the surface silanol (SiOH) groups of the silica nanoparticles can serve as both H-bond donors and acceptors, they have a potential to interact with both cations and anions of the PILs. To understand the interaction of the PILs with the surface of the silica particles, NMR and IR spectra were measured for highly concentrated composites with a V silica of 0.6, where the majority of the ions were assumed to be capable of bonding with the surface silanol groups.…”
Section: Resultsmentioning
confidence: 99%
“…In previous studies, ion adsorption of ILs on the silica surface was suggested to occur via H-bonding. ,, It has been reported that the N–H protons in the cation of PILs also form extensive and directional H bonds with anions forming H-bonded cation–anion aggregates in neat PILs. , As the surface silanol (SiOH) groups of the silica nanoparticles can serve as both H-bond donors and acceptors, they have a potential to interact with both cations and anions of the PILs. To understand the interaction of the PILs with the surface of the silica particles, NMR and IR spectra were measured for highly concentrated composites with a V silica of 0.6, where the majority of the ions were assumed to be capable of bonding with the surface silanol groups.…”
Section: Resultsmentioning
confidence: 99%
“…The important part of theoretical simulation of the functionalized silica gel with organic groups is modeling the surface of the support. Various clusters comprises silicon-oxygen sequence have been reported to model the surface of silica gel [14][15][16][17][18][19][20][21]. From them, 8-edge-atom (cubic) nanocluster is reported as the most stable geometry for modeling the surface of silica ( Fig.…”
Section: Resultsmentioning
confidence: 98%
“…To understand the acidity change observed for SiO 2 ‐IL‐SO 3 H, DFT calculation was conducted to analyze the interaction between the ionic liquid and the surface of SiO 2 . Mimicking the surface in the form of cage‐like clusters is a relatively reasonable estimation about the properties of SiO 2 , which has been widely applied in many fields . In this work, we selected 3 × (SiO 2 ) 4 as the calculation model, as depicted in Fig.…”
Section: Resultsmentioning
confidence: 99%
“…Mimicking the surface in the form of cage-like clusters is a relatively reasonable estimation about the properties of SiO 2 , which has been widely applied in many fields. [31][32][33][34] In this work, we selected 3 × (SiO 2 ) 4 as the calculation model, as depicted in Fig. S2 Fig.…”
Section: Computation Of Acidity Of Immobilized Ionic Liquidmentioning
confidence: 99%